Intersubjetividade na determinação do significado das palavras referentes às sensações: uma análise do parágrafo 244 das Investigações Filosóficas - Borges, Priscilla da Veiga (2024)
In the present work, our general objective will be to present how Wittgenstein, in paragraph 244 of the Philosophical Investigations, deals with the determination of the meaning of words referring to sensations. In this sense, in this work, we will not deal with all the themes that revolve around the term “private language argument”. The specific objective of our work will be to explore, in a more systematic way, the most difficult case of idealism, which is the determination of the meaning of the sensation of pain, which will be described, in this work, as unshared sensation. Our working hypothesis considered that, to answer the question asked in § 244 of the IF, “How do words refer to sensations?” (Wittgenstein, 2000a, p. 98), there are two types of answers: a subjective one, which Wittgenstein will criticize, and an intersubjective one, which he will accept. From the analysis of the second part of paragraph 244 of the Philosophical Investigations, we sought to show that Wittgenstein offers a possibility or alternative not based on the traditional referential model (which supposes, in terms of the word-object relationship, a private meaning for sensation), but a perspective clearly guided by the intersubjective and public character. In this sense, in the development of the work, and in accordance with the general objective already indicated, we intend to establish only interpretative parameters of an intersubjective nature to establish the meaning of words referring in two cases only, to pain sensations and color perception.